Does early detection of renovascular hypertension improve outcomes?. Issue 5 (May 2017) - Noveloso, Bernard; Reddy, Snehal; Shah, Bilal; Stelmaschuk, Nadezda
Abstract : EVIDENCE‐BASED ANSWER : Probably not. Finding atherosclerotic renal artery stenosis (ARAS) and treating with revascularization has shown no clinically significant improvement in rates of myocardial infarction (MI), renal function, congestive heart failure (CHF), or stroke compared with medical treatment of renovascular hypertension (SOR: A, metaanalysis of RCTs). Recommendations to revascularize asymptomatic ARAS are controversial, calling into question the need for early detection (SOR: C, expert opinion).